Límites al derecho de acceso a la información clínica en los casos de estado necesidad terapéutica y anotaciones subjetivas. Especial referencia al sistema español (2013)
The right to information has gained importance throughout the twentieth century, one of the pillars of health care and the physician - patient relationship, has some peculiarities, even if they have constitutional and legal recognition, far from being a absolute right. An example is in the Spanish Patient Autonomy Act limits the right when patient information enshrined, specifically two very important: the state of therapeutic need and subjective annotations. However, the law left open and willing to be debated issue.